A Training Program to Develop Strategies for Solving a Mathematical Problem and Mathematical self-Esteem Among Students in Terms of the Trends of International Examinations - Aburezeq, Khalil; Hani, Al-Agha (International Journal of Education and Cognitive Sciences, 2022)
The study aimed to examine the effectiveness of a training program that is built in terms of the trends of international examinations to develop strategies for solving mathematical problems and mathematical self-esteem among 8th, 9th and 10th graders. The students were selected from two schools in KhanYunis city in Palestine. The experimental research utilized a one-group design, using a test of mathematical problem-solving strategies and a mathematical self-esteem Scale as instrumentation. The results of the study revealed an improvement among the students taught by the strategies of mathematical problem-solving and mathematical self-esteem. In addition, the program revealed the effectiveness and effect of the strategies of solving mathematical problems, while the strategies of mathematical self-esteem showed only an effect, but not effectiveness. The results also showed a moderate positive relationship between students’ possession of problem-solving strategies and mathematical self-esteem. The results obtained were discussed in detail in the section of findings and discussion.